The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/02619768.2020.1793952
|View full text |Cite
|
Sign up to set email alerts
|

Finnish teacher educators’ preferences for their professional development – quantitative exploration

Abstract: Education makes a difference and teacher educators are an important part of that circle. However, there is very little research done in Finland on teacher educators' professional development. The main purpose of this study was to develop and test the psychometric properties of three scales that measure the components of teacher educators' professional development, namely (a) developmental needs, (b) preferred ways of fulfiling those needs and (c) hindrances to fulfiling developmental needs. The differences bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
1
5
0
1
Order By: Relevance
“…In this stage, teacher educators, who had already succeeded in gaining the required diplomas, began building their mastery in teaching and confidence in research; contrarily, those failing to get further education faced losing commitment to the profession by focusing more on side jobs. Those who attempted to develop a sense of self-efficacy became more active in communicating with their colleagues in and out of their university and engaged in research projects, which concurs with previous studies (Byman et al, 2021; Van der Klink et al, 2017). In Vietnam, male teacher educators are more active and have more time to engage because they are not burdened by family duties.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this stage, teacher educators, who had already succeeded in gaining the required diplomas, began building their mastery in teaching and confidence in research; contrarily, those failing to get further education faced losing commitment to the profession by focusing more on side jobs. Those who attempted to develop a sense of self-efficacy became more active in communicating with their colleagues in and out of their university and engaged in research projects, which concurs with previous studies (Byman et al, 2021; Van der Klink et al, 2017). In Vietnam, male teacher educators are more active and have more time to engage because they are not burdened by family duties.…”
Section: Discussionsupporting
confidence: 87%
“…They acknowledge the significance of research for their professional development and reputation, which differs from early-career teacher educators’ perceptions. These experts are more inclined to join in or lead a group research endeavor and professionally interact with external experts rather than to peer-coach or participate in courses (Byman et al, 2021). They are interested in contributing to the profession, enabling knowledge development, and learning by publication (Shagrir, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Karlberg and Bezzina (2022) explored the effect of different perspectives of teachers with varying levels of experience on their professional development. Byman et al (2021) found significant differences in opportunities and satisfaction with CPD among teachers with different professional titles. Meanwhile, Yuan and Tian (2023) discovered significant differences in the professional development of teachers with varying educational backgrounds, work experience, and professional titles, manifest in the enhancement of their level of professional development with increased work experience and promotion.…”
Section: Cpd Among Teachers With Different Educational Backgrounds Pr...mentioning
confidence: 86%
“…It is a prerequisite of the transformation of knowledge and exchange of practices in the teacher learning process (Giddens, 1984), and plays a central role in CPD (Wagner et al, 2019). Further research reveals that individual teachers' characteristics, including education, academic title and work experience, all influence their CPD (Byman et al, 2021;Coenders & Verhoef, 2019;Mikkonen et al, 2018). Therefore, the aim of this study is to explore the impact of teacher education, academic titles, work experience and agency on CPD.…”
Section: Introductionmentioning
confidence: 99%
“…Selain itu, diperlukan juga kreativitas dalam berinovasi untuk mengembangkan sekolah serta meningkatkan prestasi belajar siswa. (Rahmawati & Syamratulangi, 2020) Menurut penelitian tentang pengembangan profesionalisme bagi pendidik dan tenaga kependidikan, menurut (Byman et al, 2020) dikemukakan bahwa profesionalisme dan pekerjaan guru memiliki keterkaitan yang erat. Seperti yang diungkapkan sebelumnya, berbagai bidang pekerjaan memiliki kebutuhan pengembangan profesional yang berbeda di antara para pendidik dan tenaga kependidikan saat ini.…”
Section: Pendahuluanunclassified